Chenneville : [large type] a novel of murder, loss, and vengeance - Jiles, Paulette, 1943- (Thorndike Press large print historical fiction., 2023)
Union soldier John Chenneville suffered a traumatic head wound in battle. His recovery took the better part of a year as he struggled to regain his senses and mobility. By the time he returned home, the Civil War was over, but tragedy awaited. John's beloved sister and her family had been brutally murdered. Their killer goes by many names. He fought for the North in the late unpleasantness, and wore a badge in the name of the law. But the man John knows as A. J. Dodd is little more than a rabid animal, slaughtering without reason or remorse, needing to be put down. Traveling through the unforgiving landscape of a shattered nation in the midst of Reconstruction, John braves winter storms and confronts desperate people in pursuit of his quarry. Untethered, single-minded in purpose, he will not be deterred. Not by the U.S. Marshal who threatens to arrest him for murder should he succeed. And not by Victoria Reavis, the telegraphist aiding him in his death-driven quest, yet hoping he'll choose to embrace a life with her instead. And as he trails Dodd deep into Texas, John accepts that this final reckoning between them may cost him more than all he's already lost ...